Design and usability of a system for the study of head orientation - Chen, Ji; Wright, William Geoffrey; Keshner, Emily; Darvish, Kurosh (Frontiers in Rehabilitation Sciences, 2022)
The ability to control head orientation relative to the body is a multi-sensory process that mainly depends on three sensory pathways namely, proprioceptive, vestibular, and visual. A system to study the sensory integration of head orientation was developed and tested. A test seat with five-point harness was assembled to provide the passive postural support. A light-weight head-mount display (HMD) was designed for mounting multi-axis accelerometers and a mini- CCD camera to provide the visual input to virtual reality (VR) goggles with 39° horizontal field of view. A digitally generated sinusoidal signal was delivered to a motor-driven computer-controlled sled on a 6m linear railing system. A data acquisition system was designed to collect acceleration data. A pilot study was conducted to test the system. Four young healthy subjects were seated with their trunks fixed to the seat. Subjects received a sinusoidal anterior-posterior translation with peak acceleration of 0.06g at 0.1Hz and 0.12g at 0.2Hz, 0.5Hz and 1.1Hz. Four sets of visual conditions were randomly presented along with the translation. These conditions included eyes open looking forward, backward, and sideways, and also eyes closed. Linear acceleration data were collected from linear accelerometers placed on the head, trunk and seat and were processed using MATLAB. The head motion was analyzed using Fast Fourier Transform (FFT) to derive gain and phase of head pitch acceleration relative to seat linear acceleration. A randomization test for two independent variables was used to test significance of visual and inertial effects on response gain and phase shifts. Results show that the gain was close to one with no significant difference among visual conditions across frequencies. The phase was shown to be dependent on the head strategy each subject use.